Epidemiological Patterns of Schistosomiasis in North Central Nigeria: A Systematic Review of Prevalence, Risk Factors, and Control Strategies - Aladodo, Raliat A.; Mohammed, Abdulquadri; Ibrahim, Rasheed B.; Alabi, Mutiu A. (Researchers Journal of Science and Technology, 2026)
Schistosomiasis remains one of the most important neglected tropical diseases and constitutes a persistent public health challenge in Nigeria, which bears the highest global burden of infection. Although numerous epidemiological studies have been conducted in North Central Nigeria, no previous systematic review has comprehensively synthesized regional evidence on disease prevalence, associated risk factors, diagnostic approaches, and control strategies. This systematic review therefore aimed to synthesize the available evidence on the epidemiological patterns of schistosomiasis in North Central Nigeria to provide region-specific evidence for disease control and policy. The review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. A comprehensive search of Google Scholar, PubMed, African Journals Online (AJOL), and ScienceDirect was performed to identify eligible studies published between January 2000 and July 2026. Methodological quality was assessed using the Joanna Briggs Institute (JBI) Critical Appraisal Checklist for prevalence studies, and findings were synthesized narratively because of substantial heterogeneity among included studies. Nineteen studies involving 13,729 participants across six states and the Federal Capital Territory met the inclusion criteria. The included studies demonstrated moderate to high methodological quality, with JBI quality scores ranging from 5 to 7 out of 9. Reported prevalence ranged from 2.07% to 77.4%, with Schistosoma haematobium identified as the predominant species and school-aged children representing the most affected population. Frequent contact with contaminated freshwater bodies was the most consistently reported risk factor, while urine filtration and the Kato–Katz technique were the principal diagnostic methods. Mass drug administration with praziquantel, health education, and improvements in water, sanitation, and hygiene (WASH) were the most frequently recommended control strategies. These findings highlight the need for strengthened integrated schistosomiasis control programmes that combine preventive chemotherapy with improved WASH infrastructure, health education, snail control, and enhanced surveillance to support progress toward the WHO 2030 elimination targets. This review is the first to systematically synthesize epidemiological evidence specifically for North Central Nigeria, thereby providing region-specific evidence to guide public health planning and resource allocation. However, interpretation of the findings should consider the substantial heterogeneity in study designs, populations, and diagnostic methods, which precluded quantitative meta-analysis and limited direct comparison across studies.